Silent crickets: A new genus of Neometrypini from the Brazilian Atlantic Forest (Orthoptera: Oecanthidae: Tafaliscinae) - Almeida, Vitor Tonon De; Souza-Dias, Pedro G. B.; Nihei, Silvio Shigueo; Campos, Lucas Denadai De (Zootaxa, 2025)
A new genus of oecanthid cricket from the Neometrypini tribe is described here: Aphonodiacanthus Tonon & Campos gen. nov., comprising three new species: A. melanocephalus Tonon, Campos & Souza-Dias sp. nov., A. maculatus Tonon & Campos sp. nov., and A. chlorops Tonon & Campos sp. nov., from the Brazilian states of Paraná, Bahia, and São Paulo respectively. The combination of male genitalia characters, mainly the pointed shape of the pseudepiphallic lateral lobes, and other morphological features such as the short forewings and supra anal plate, supports the proposal of this new genus. A geographical distribution map and identification key to species are provided, along with an updated identification key to genera of Neometrypini. A brief discussion is also presented for traits such as the subgenual organ, the absence of acoustic communication, the metanotal glands, and highlight the presence of A. chlorops Tonon & Campos sp. nov. in a densely populated area within the São Paulo metropolitan region, inhabiting an urban fragment of Atlantic Forest.